Design of a planar structure of multifrequency patch antenna - Alam, A. H. M. Zahirul; Islam, Md. Rafiqul; Khan, Sheroz (CSES Internationa, 2008)
A planar multiband microstrip antenna is proposed in this work. The proposed antenna structure comprises a center patch antenna known as driven patch and two adjacent microstrip patches defined as wing patches. The effect of gap between driven patch and the wing patches have been studied for multiband frequency operation. The antenna is operated at 2.79GHz, 3.77GHz, 4.28GHz, 4.97GHz and 5.69GHz if there is no gap between the driven patch and the wing patch. The antenna can be operated at 2.41GHz and 6.67GHz by incorporating gap between the driven patch and the wing patch.